1980
DOI: 10.2307/1936822
|View full text |Cite
|
Sign up to set email alerts
|

Energy Flow and Grazing Behavior of Conocephaline Grasshoppers in a Juncus Roemerianus Marsh

Abstract: At least three species of conocephaline grasshoppers (Tettigoniidae) form the major grazing herbivores on the leaves of the marsh black needlerush Juncus roemerianus Scheele. They ingested 105 kJ/m 2 of the 31.62 MJ/m 2 net annual aboveground production of Juncus. Assimilation of ingested Juncus tissue was 60.7 kJ · m-2 • yr-' and production of new tissue by the grasshoppers was 9.6 kJ · m-2 • yr-1 , which represents 0.03% of the net annual primary production. A secondary effect of grazing was manifested by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…O. fidicinium appears to be limited to the S. alterniflora zone. Given that O. concinnum was found much more frequently in the Juncus than the Spartina zone, it appears to be a specialist herbivore on J. roemerianus (Parsons and de la Cruz 1980), along with C. aigialus. These two tettigoniid species appear to be transient visitors to the S. alterniflora zone.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…O. fidicinium appears to be limited to the S. alterniflora zone. Given that O. concinnum was found much more frequently in the Juncus than the Spartina zone, it appears to be a specialist herbivore on J. roemerianus (Parsons and de la Cruz 1980), along with C. aigialus. These two tettigoniid species appear to be transient visitors to the S. alterniflora zone.…”
Section: Discussionmentioning
confidence: 97%
“…Studies with high-latitude tettigoniid assemblages, likely dominated by C. spartinae, have concluded that they feed mostly on seeds and flowers, and thus, influence plant communities by impacting sexual reproduction more than somatic growth (Bertness et al 1987;Bertness and Shumway 1992). In contrast, studies with low-latitude tettigoniid assemblages, likely dominated by O. fidicinium (Georgia S. alterniflora zone) and O. concinnum (Mississippi J. roemerianus zone), have focused on consumption of leaves (Smalley 1960;Parsons and de la Cruz 1980). These patterns were confirmed in our laboratory feeding assays using southern S. alterniflora and J. roemerianus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the percent aerial cover of dominant vegetation types within 50 m of each nest site was estimated visually (methods described in Conway 2008). Prey items included gastropods (olive nerite Neretina usnea and marsh periwinkle Littorina irrorata), bivalves (ribbed mussel Geukensia demissa and common rangia Rangia cuneata; Bishop and Hackney 1987;LaSalle and de la Cruz 1985), tettigoniid grasshoppers (Parsons and de la Cruz 1980), blue crab (Callinectes sapidus), and gulf fiddler crab (Uca longisignalis; Mouton and Felder 1996). All materials were placed in individual plastic bags and frozen within several hours of collection.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Varley (1967) has shown that feeding by tissue-chewing lepidopteran larvae can reduce standing biomass of plants, and Weigert and Pomeroy (1981) speculate that the same is true for salt marsh plants. Other authors (Gallagher and Pfeiffer 1977, Crow and McDonald 1978, Parsons and de la Cruz 1980 have questioned whether significant portions of wetland standing crops are affected by herbivory.…”
Section: Introductionmentioning
confidence: 99%